A novel Schiff base macrocycle based on 1, 1′‐binaphthyl for fluorescence recognition. (19th June 2021) - Tokunaga, Hiroki; Kazama, Kotoha; Tsuboi, Masaki; Miyasaka, Makoto
Abstract: A novel chiral polyimine macrocycle C‐1 was designed and synthesized by the self‐condensation of the dialdehyde of the chiral dinaphtho[ 2, 1‐d:1′, 2′‐f ][1, 3]dioxepine derivative and o ‐phenylenediamine by Schiff base formation, and the corresponding polyamine macrocycle C‐1H was obtained by the reduction of the polyimine macrocycle. The UV–vis and fluorescence spectral studies indicated that both C‐1 and C‐1H form the complex with metal ions in a 1:2 ratio. The fluorescence behaviour of C‐1 upon the addition of Zn 2+ or Cd 2+ showed a 'turn‐on' response accompanied by fluorescence enhancement at 510 nm six times for Cd 2+ and 13 times for Zn 2+ . In contrast, C‐1H revealed a 'turn‐off' response upon the addition of Co 2+, Ni 2+, and Cu 2+ . Abstract : Novel chiral polyimine macrocycle C‐1 and corresponding polyamine macrocycle C‐1H were synthesized. The fluorescent behavior of C‐1 upon the addition of Zn 2+ or Cd 2+ showed a "turn‐on" response accompanied with fluorescence enhancement at 510 nm by 6 times for Cd 2+ and by 13 times for Zn 2+ . On the contrary, C‐1H revealed a "turn‐off" response upon the addition of Co 2+, Ni 2+, and Cu 2+ .